Formulation And Sensory Evaluation of Waterchestnut Flour Laddoo - Shalini,; Raghav , Pramod K (Journal of Postharvest Technology, 2022)
After chestnut flour was used to prepare Ladoo by incorporating processed water chestnut through  sun drying, water chestnut flour Ladoo was standardized with different percentages of water chestnut  flour. The percentages used were 0% (T0 as control), 5% (SDT1), 10% (SDT2), 15% (SDT3), and  20% (SDT4), respectively. Water chestnut flour incorporated Ladoo with 0% water chestnut flour  was treated as the control. The nutritional contents of the sun-dried water chestnut flour were  evaluated using AOAC methods. The proximate composition of SDT (sun-dried water chestnut flour  treatment) for moisture content, protein, fat, total ash, crude fiber, and carbohydrate were 11.02 g,  12.42 g, 3.44 g, 2.93 g, 0.54 g, and 70.19 g, respectively. Water chestnut flour is a potential source  of potassium and calcium, with levels of 1298.64 mg/100g and 89.26 mg/100g, respectively. The  water chestnut flour showed good antioxidant content. In the evaluation of sensory characteristics  of water chestnut Ladoo, a significant difference (P
Keywords: Water chestnut flour; Singhara; Trapa natans; Ladoo; Antioxidants; Minerals; Sensory attributes